2020
DOI: 10.12998/wjcc.v8.i18.4022
|View full text |Cite
|
Sign up to set email alerts
|

First-line chemotherapy in very elderly patients with metastatic pancreatic cancer: Gemcitabine monotherapy vs combination chemotherapy

Abstract: BACKGROUND Combination chemotherapy (gemcitabine plus nab-paclitaxel and FOLFIRINOX) is widely used as the standard first-line treatment for pancreatic cancer. Considering the severe toxicities of combination chemotherapy, gemcitabine monotherapy (G mono) could be used as a first-line treatment in very elderly patients or those with a low Eastern Cooperative Oncology Group status. However, reports on the efficacy of G mono in patients older than 75 years are limited. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…First, we analyzed the binding potency of the active components and target proteins by molecular docking. Gemcitabine, a tumor chemotherapy drug whose intracellular metabolites bind to DNA and act primarily in the G1/S phase [ 22 , 23 ], was selected for docking with the core targets. Also, the binding potency data worked as a baseline for positive control.…”
Section: Resultsmentioning
confidence: 99%
“…First, we analyzed the binding potency of the active components and target proteins by molecular docking. Gemcitabine, a tumor chemotherapy drug whose intracellular metabolites bind to DNA and act primarily in the G1/S phase [ 22 , 23 ], was selected for docking with the core targets. Also, the binding potency data worked as a baseline for positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Despite variations in the definition of "elderly" and the study population across different studies, the findings consistently indicate that no significant difference was found between the elderly and young patients in terms of OS and PFS. 7,[9][10][11][12]14,15,17,[21][22][23] In previous studies, the reported OS for elderly patients treated with nab-paclitaxel plus gemcitabine ranged from 8.5 to 12.0 months, 7,9,11,14,22 whereas for FOLFIRINOX, the reported OS ranged from 11.6 to 13.3 months. 15,21,23 Similarly, the reported PFS for nab-paclitaxel plus gemcitabine ranged from 5.5 to 7.2 months, 7,9,11,14 whereas for FOLFIRINOX, it ranged from 3.7 to 10.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, few studies on elderly patients with PDAC who received FOLFIRINOX or nab-paclitaxel plus gemcitabine in Korea have been conducted. 17,18 Therefore, this study aimed to compare the efficacy and toxicity of FOLFIRINOX and nab-paclitaxel plus gemcitabine in elderly patients with advanced PDAC with that of younger patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Han и соавт. ретроспективно оценили эффективность моно-и комбинированной химиотерапии гемцитабином у 104 пациентов пожилого и старческого возраста [15]. В группе пациентов пожилого возраста медианы ВБП и ОВ были значительно выше при комбинированной химиотерапии, чем при монотерапии гемцитабином.…”
Section: ' 2022unclassified